Improving the costing system at FCI: an operations perspective - Horn, Micheal Oskar (Engineering Management, 2024)
This thesis is an attempt to derive a more effective management accounting system to meet the contemporary organisation's needs. The objective of the thesis is to investigate two management accounting approaches, activity based costing and cost reduction system. Further, to evaluate which one better suits the needs of FCI, a clothing manufacturer in the Western Cape, and also to develop and test a costing system which forms the basis of any management accounting system. Soft systems methodology was used to evaluate the two approaches. It was found that activity based costing (ABC) is more appropriate in this situation, mainly because the cost reduction system requires an organisational culture of employee involvement and continuous improvement, which is currently lacking. The ABC system for FCI was developed with the specific aim of separating garment related costs (production) from order related costs (sales and design). This, however, was done within the constraints of the information available and the number of cost drivers was therefore limited to seven. The simplicity of the new system will enhance its transparency. Reasons for variations in cost estimations from the current system can be identified. This reduces the potential resistance to accept the new system for decision making. The proposal of the ABC system was tested in two different experiments, namely a computer simulation and a test with real data. The simulation was done using a systems dynamics modelling (SDM) software package. The SDM model showed that the proposed ABC system improves the accuracy of cost estimations. It also showed that the improvement of the cost estimations is dependent on the quality of the cost driver and the accuracy of the input information. The test with real data was done on a spreadsheet which automated the costing procedure. The spreadsheet contained information about the bill of activities, budget forecasts and output levels of activity pools and can, without further adaptation, be used as a temporary means to determine costs once ABC is introduced. Costing a sample of orders with the spreadsheet showed the effect of the order quantities. ABC estimates costs of a small order to be higher than the current system predicts. This is especially the case for high fashion garments requiring significantly more design and sales resources. The test also revealed that ABC cost estimations of garments with a high sewing content (high SMV) are lower than estimations by the current system. This is in accordance with the expectations, which gave rise to the investigation into alternative costing methods. Product and customer profitability analysis of the sample of orders showed the typical trend. Some products/customers are highly profitable, the majority yield an acceptable profit, but some are produced at a loss. Both experiments show that the ABC system for FCI was developed successfully. It is recommended that the proposed ABC system be implemented and used concurrently with the current system until confidence is gained with regard to the validity of the estimations. It is also recommended that the system be continuously improved by improving the input information and introducing better cost drivers and more activity pools.